Dinamika Beban Ganda Karyawan Perempuan pada Era Work From Home dan Hybrid Working - Bintang Mutiara Maharani; Diah Ayu Retno Palupi; Rafika Meilia Sari (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to examine how the double burden experienced by female employees has changed in the era of work from home (WFH) and hybrid working. The method used is a Systematic Literature Review (SLR) by systematically reviewing and selecting 10 relevant national scientific articles related to double burden, work-family conflict, and flexible working systems published between 2021–2026. The collected data were analyzed using a thematic analysis approach to identify major themes related to work flexibility, domestic responsibilities, organizational support, and work-life balance. The results of this study provides an overview of the dynamics of women’s double burden within flexible working systems by showing that WFH and hybrid working do not always create work-life balance, but can also increase work-family conflict, psychological pressure, and the blurring boundaries between work and personal life. This study also strengthens discussions regarding the influence of work digitalization on the changing patterns of women workers’ double burden in the modern work environment. In addition, less adaptive organizational policies and limited support further intensify the complexity of the double burden. These findings indicate that without proper management, flexible work arrangements may become a new source of pressure. Therefore, human resource management needs to play a more active role in designing responsive policies that support better role balance.